Estimates of thyroid cancer incidence in Brazil: an approach using polynomial models - Alexandre dos Santos Brito; Cláudia Medina Coeli; Flávia dos Santos Barbosa; Rosangela Caetano; Marceli de Oliveira Santos; Mario Vaisman (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
This study aimed to estimate thyroid cancer incidence in Brazil in 2006 using polynomial models that take age and birth cohort effects into account in the estimation process. Estimates were based on new cases of thyroid cancer in nine Brazilian cities (Manaus, Palmas, Natal, Recife, Cuiabá, Belo Horizonte, São Paulo, Porto Alegre, and Curitiba) and the Federal District from 1997 to 2001. We estimated 6,066 new cases, of which 1,065 in men and 5,001 in women. The incidence rates were, respectively, 1.16 and 5.27 per 100,000 inhabitants. Rates increased with age in both genders, especially after 30 years. The size and profile of rates according to age and gender indicate that the method yields plausible estimates.